PENYIDIKAN OLEH KEPOLISIAN TERHADAP PENYALUR JASA TENAGA KERJA INDONESIA ILEGAL DI WILAYAH HUKUM POLISI DAERAH KEPULAUAN RIAU - Handayani, Silvia; Edorita, Widia; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Until now the criminal act of illegal placement of migrant workers by thebrokers still occur in the area of Kepulauan Riau Police especially in Batam City,because Batam City is used as a transit point for them to go to Singapore orMalaysia through the official international transportation route where using aregular passport with mode that their destination is limited to visiting destinationcountries, this reasoning used to trick immigration officers. The criminal act ofillegal placement of migrant workers conducted by brokers or service providers inthe Kepulauan Riau Police territory in 2015 the number of suspects as many as 4people with the number of victims as many as 17 people, in 2016 the number ofsuspects as many as 13 people with the number of victims of 66 people, and in 2017the number of suspects as many as 4 people with the number of victims as many as22 people.This research is a type of research that is empirical or sociological lawresearch. Legal juridical empirical research or sociological law research is researchconducted directly on site or in the field to obtain data to provide a complete andclear picture of the problem in the perusal. Viewed from its nature describes the factsof symptoms and facts contained in life in a deep social.The results of research conducted by the author is first, the investigation ofthe Indonesian labor supplier in the Batam City handled by Kepulauan Riau Policeis not optimal. Second, obstacles from lack of knowledge and legal awareness of thecommunity, searching for illegal migrant worker recruiters, facilities andinfrastructure, lack of operational budgets, fewer police officers and no legal degree.Third, efforts to overcome these obstacles by increasing participation and knowledgewith the socialization of law to the community, coordinate with local police to lookfor the presence of suspects illegal recruiters, improve facilities and infrastructure,increase operational budget, increase the number of police officers and policeshould have law degree.Keywords: Investigation - Criminal Act - Labor - Illegal